The Linked Data and the Discovery of Links in the Bibliographic Universe - Ávila Barrientos, Eder (2019)
The bibliographical universe is a complex context and is in a constant evolution. It is formed by entities, data and relations of bibliographical affairs. Librarianship, or library science, has studied this universe from the documentary organization perspective. It’s been identified that the information technologies have influenced deeply in this universe, causing the appearance of new sources giving the remarkable importance of the information that conforms them. The bibliographical universe and the semantic web are parallel environments that can count with connection patterns. To this effect, it is necessary for the library regulations to be adapted to the early semantic web. Linked Data is a model for the generation, publication and entailment of structured data in the web. This model has been identified by the librarian community and has been adapted to the BIBFRAME and LRM-IFLA conceptual models. Therefore, the focus of this work remains on analyzing the application of Linked Data elements to identify the patterns that allow the discovery of existent data links in the library universe. The obtained findings of the application and integrations of Linked Data principles in the librarian register are presented, and the derivative concept of linked bibliographical data is explained.